Study of obstetric and fetal outcome of post caesarean pregnancy - Nigam, Akanksha; Anand, Rakesh; Jain, Niyati (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: With the sky rocketing caesarean section rates an increasing number of women face the issue of mode of delivery in their current pregnancy. There are conflicting reports regarding the safety of a trial for Vaginal Birth After Caesarean delivery (VBAC) in terms of uterine rupture and concern about, maternal and perinatal morbidity. The purpose of this study was to evaluate the obstetric and fetal outcomes of patients presenting at term with a history of previous LSCS. Methods: A one year prospective observational study was conducted where in all patients who had a term pregnancy with a history of prior LSCS were included in the study after obtaining their consent for participation. The obstetric and fetal outcomes of these patients in the present pregnancy were noted and tabulated. A descriptive analysis of these outcomes was carried out. Results: 100 patients at term, with a history of previous LSCS were studied. Of these, trial for a VBAC was attempted by 50 patients of these 46% (23) had a successful VBAC. And remaining 54% went for emergency LSCS. 50% patients underwent an elective repeat caesarean deliver. Scar dehiscence was seen in 2.72% of the patients who opted for a trial for VBAC. Perinatal morbidity was higher in cases of repeat caesarean delivery than in those who had a successful VBAC (12.12% vs. 0 percent). Maternal complications were also higher in patients who had a repeat LSCS compared to those who had a successful VBAC. Conclusions: With an increase in the proportion of patients with a history of previous LSCS, it is essential for health care institutions to have proper antenatal counseling regarding VBAC and a well-defined management protocol in place in an effort to increase the number of VBACs and bring down the overall caesarean rates. Patients with a history of prior vaginal delivery have an increased likelihood for a successful VBAC. A successful VBAC is associated with a lower perinatal and maternal morbidity than repeat caesarean delivery, and this is relevant for counseling women about their choices after a caesarean delivery.